The Coexistence Between Matrilineal Family Structures and the Religious Order of the Minangkabau Community - Dwi Rini Sovia Firdaus (Ikatan Sarjana Komunikasi Indonesia, 2019)
Minangkabau customary law is always quite open to integrating with new elements. Despite the influences of Hinduism, Buddhism, and colonial ruler, it is Islam that has encouraged the lifestyle of the matrilineal community until now. The meeting of the elements has created the term ‘adat bersendi syarak, syarak bersendi kitabullah’, which clearly shows a marriage between old elements and new ones. It seems that this process did not stop there since social change continues to occur in line with the influence of globalization. Despite the ongoing social change, the Minangkabau society still have the strong will to preserve the core elements of their culture. This research was conducted at Nagari Maninjau and Nagari Sungai Batang. Each population referred to in this research means a family group consisting of a father, a mother, and at least one child aged 10-19 years. This study uses a simple quantitative method, involving a total of 106 families as respondents. The results of interview were further analyzed qualitatively. The pioneer of cultural preservation is urban area. In terms of loyalty to introduce culture to the next generation, the family configuration of Minang father+Minang mother and non-Minang father+Minang mother fulfill the criteria. Data shows that no uncle plays a significant role in inheriting culture since the central role is played by a mamak pusako.